Design, Fabrication, In Vitro and In Vivo Assessment of Aloe vera Containing Transgel for Delivery of Meloxicam - Powar, Trupti A. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Aim of the present investigation is to develop meloxicam incorporated Aloe vera gel (MAG) and to study its pharmacodynamics and in vitro evaluation studies. Materials and Methods: 23 factorial design was used to optimize the independent variables as amount of hydroxy propyl methyl cellulose (HPMC) (X1), amount of carboxy methyl cellulose (CMC) (X2), and amount of Carbopol 934 (X3) as gelling agent at varying concentration, i.e. 1% and 2%. Total 8 batches (F1-F8) were prepared and evaluated for gel consistency, spreadability, drug content, physicochemical parameters such as pH, viscosity, and in vitro diffusion assessment. Pharmacodynamic activity of MAG (batch F8) was evaluated in Wistar albino rats and compared with commercially available marketed cream (MC) against the same parameters. Results: Batch F8 containing a higher concentration of Carbopol 934, HPMC, and CMC shows improved gel consistency, with good spreadability, viscosity, and drug content. These results indicate the suitability of 23 factorial design for fabrication of MAG. Noteworthy, batch F8 showed significant (P < 0.05) in vitro drug release (76.72%) compared to marketed formulation (70.56%) at 150 min. Percentage inhibition of edema was greater for the batch F8 (26.48%) compared to MC (20.32%) after 60 min. This improved efficacy might be due to direct stimulation of the activity of macrophages and fibroblasts by A. vera gel and binding of mannose 6-phosphate to the growth factor receptors on the surface of the fibroblasts, thereby promoting tissue repair. Conclusion: Hence, decisively A. vera gel serves as an effective gel base to incorporate meloxicam with high drug loading capacity.